The Economics of Happiness: Exploring the Complex Relationship Between Income and Subjective Well-Being - Hudson-Reed, Jessica Erin (School of Economics, 2019)
Over the past decade, economists and policy makers have become increasingly interested in the relationship between income, economic growth and happiness. Drawing on the existing literature and empirical evidence, this research seeks to contribute to a better understanding of the complex relationship between income and subjective well-being. This research uncovers a paradoxical relationship between income and subjective well-being. Specifically, at a point in time, both within and across nations, happiness varies directly with income, but over time, happiness does not increase when a country’s income increases. This paradoxical relationship can be attributed to 'internal’ and 'external’ income comparisons and the effects these comparisons have on material aspirations and satisfaction judgements. As such, this research finds that relative income, in addition to one’s own absolute income, is an important determinant of individual subjective well-being. Moreover, this research provides evidence of a possible causal relationship between income, relative income and subjective well-being. Overall, this research makes a valuable contribution to the literature by bringing together a diverse range of empirical evidence and theoretical arguments to form a holistic and indepth understanding of the complex relationships and processes at work.